Focalization schemas, transnational formations and social remittance in the works of Chimamanda Ngozi Adichie - Maritim, Eric Cheruiyot (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.